2012
DOI: 10.1371/journal.pone.0035631
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that Prefibrotic Myelofibrosis Is Aligned along a Clinical and Biological Continuum Featuring Primary Myelofibrosis

Abstract: PurposeIn the WHO diagnostic classification, prefibrotic myelofibrosis (pre-MF) is included in the category of primary myelofibrosis (PMF). However, strong evidence for this position is lacking.Patients and MethodsWe investigated whether pre-MF may be aligned along a clinical and biological continuum in 683 consecutive patients who received a WHO diagnosis of PMF.ResultsAs compared with PMF-fibrotic type, pre-MF (132 cases) showed female dominance, younger age, higher hemoglobin, higher platelet count, lower w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
71
2
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 42 publications
9
71
2
3
Order By: Relevance
“…Since younger age in MF is mostly associated with an indolent disease phenotype characterized by normal or increased hemoglobin value and thrombocytosis [38], by multivariable analysis we established that younger age and increasing platelet count were both independent covariates associated with higher eNAMPT levels. These data indicate that increased level of eNAMPT have a role in the mechanism by which young patients in MPN-associated myelofibrosis tend to have a hyperproliferative phenotype of the disease.…”
Section: Discussionmentioning
confidence: 87%
“…Since younger age in MF is mostly associated with an indolent disease phenotype characterized by normal or increased hemoglobin value and thrombocytosis [38], by multivariable analysis we established that younger age and increasing platelet count were both independent covariates associated with higher eNAMPT levels. These data indicate that increased level of eNAMPT have a role in the mechanism by which young patients in MPN-associated myelofibrosis tend to have a hyperproliferative phenotype of the disease.…”
Section: Discussionmentioning
confidence: 87%
“…Similarly, it has been suggested that prefibrotic MF may represent a transitional point between ET and MF. 129 Our understanding of the biological complexity underpinning MPNs and how this relates to clinical parameters and outcomes continues to improve. The ongoing challenge will be to integrate our understanding of these molecular processes into everyday clinical practice in order to allow for better refinement of our diagnostic classifications as well as improved prognostication and therapeutics.…”
Section: A B Cmentioning
confidence: 99%
“…[1][2][3][4][5] These myeloproliferative neoplasms have highly variable propensities to either present with or to develop progressive bone marrow fibrosis: this fibrosing process is intrinsic to primary myelofibrosis and affects a significant subset of polycythemia vera patients and a very small subset of essential thrombocythemia patients. [6][7][8][9][10][11][12] Bone marrow fibrosis is measured by reticulin and trichrome stains of the bone marrow trephine biopsy and is graded on a semiquantitative scale. 13 The classification proposed by the World Health Organization (WHO) and updated in 2008 employs the European Consensus System to grade bone marrow fibrosis, which has four possible grades (0, 1, 2, and 3); distinction between these levels is based on the number, density, and thickness of silver-stained reticulin fibers as assessed by the pathologist (Table 1).…”
mentioning
confidence: 99%